Knowledge Management -- A Tool for Risk Management - Negi, Ruchi; Bisht, Rekha (SFIMAR Research Review, 2016)
Today's Business Environment is characterized by continues radical change. Such a volatile climate demands a new attitude and approach within organizational actions, must be anticipatory adaptive and based on a faster cycle of knowledge creation. So what is the Competitive advantage today for such compan ies to survive - KNOWLEDGE MANAGEMENT. Knowledge management is about survival in a new business world - a world of complexiiy and uncertainty each day, a world which falls under the trap of shortened product life cycle, takeovers and mergers, declining revenues, lowerdemands and so on. Knowledge m anagement is the process of capturing andm aking use of firms collective expertise anywhere in the business on paper, in documents, in database or in peoples head. It is a fuel or raw material for innovation or one could say one of the systems to avert Risk. The goal is to capture the tacit knowledge required by a business process and encourage knowledge workers to share and communicate knowledge with peers. With such knowledge it is more easier to determine which process are more effective or less effective than others. In this paper an attempt is made to study KNOWLEDGE MANAGEMENT AS A TECHNIQUE TO AVOID RISKor in otherwords KNOWLEDGE MANAGEMENT ISATOOL WHICH HELPS IN RISK MANAGEMENT.